INSTITUTE OF MEDIATION IN UKRAINE DEVELOPMENT PROSPECTS AND FOREIGN EXPERIENCE - Череватюк, Вікторія Богданівна; Яценко, Альона Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the purpose of the scientific article is to generalize the foreign experience of the development of the institute of mediation and outline the prospects for the development of mediation in Ukraine. Methods: to achieve this goal, general and special scientific (special) methods were used, in particular such as: comparative law, system-structural methods, as well as the method of analysis of current domestic, foreign and international legislation. Results: despite numerous studies on this issue, the institute of mediation is of scientific interest in its further development in Ukraine. For serious changes, it is necessary to consolidate the existence of the institution of mediation at the legislative level and adopt the Law on Mediation. The issue of training professional mediators remains unresolved, so it is still important to determine that a mediator should obtain higher legal education. Discussion: despite the lack of a relevant law and the definition of the concept of «mediation» in the legislation, it is still included in the Ukrainian legislation and is used in practice. In Ukraine, there is no specialized law that would regulate the mediation procedure. Today there is only the Bill «On Mediation» adopted in the first reading. Despite the lack of a definition of «mediation» in the legislation, it is still included in Ukrainian legislation. Thus, the Civil Procedure Code, the Commercial Procedure Code, the Code of Administrative Procedure of Ukraine and the Criminal Procedure Code of Ukraine contain provisions that fully cover the dispute resolution with participation judges, the conclusion of an amicable agreement and the prohibition to interrogate as a witness persons who «are obliged by law to keep confidential information entrusted to them in connection with the provision of professional legal assistance or mediation services during out-of-court settlement of a dispute». It is very important that despite the lack of law, the profession of mediator is still recognized and added to the National Classification of Occupations of Ukraine ДК 003:2010 under number 2442.2 «Specialist in conflict resolution and mediation in the socio-political sphere». In addition, due to the active mediation practice in Ukraine, during the years of independence, mediator organizations, training centers for future mediators began to function, training and advanced training programs were developed and even the Code of Ethics of Mediators was concluded by the National Association of Mediators of Ukraine. Of course, this Code is mandatory only for members of the Association, but in the future it may become a prototype for a mandatory Code of Ethics.